Transcriptional regulation of the 5-HT1A receptor gene by deformed autosomal regulatory factor 1 - Czesak, Margaret (University of Ottawa (Canada), 2010)
Major Depressive Disorder (MDD) is the most commonly diagnosed psychiatric illness, occurring in 15-20% of the population and is characterized by prolonged mood quality impairment. It is a multifactorial disease and both genetic and environmental factors contribute to its etiology. Evidence suggests that impaired serotonin (5-HT) neurotransmission is an important underlying cause of depressive disorder. The 5-HT1A receptor is a powerful regulator of both pre and post-synaptic 5-HT neurotransmission, and becomes compromised in depression. Evidence suggests that alterations in 5-HT1A gene expression observed in depression result from compromised transcriptional regulation of the 5-HT1A receptor gene. As such, genetic variations and factors involved in the transcriptional machinery that drives 5-HT1A receptor expression are expected to playa key role in establishing normal behavioural phenotypes. I initially characterized the regulatory properties of two transcription factors, Deaf-1 and Hes-5, which have previously been shown to bind the 5-HT1A promoter region spanning a 26-bp palindrome sequence that encompasses a C(-1019)G polymorphism. Using reporter assays, I established Deaf-1 as a cell type specific regulator of the 5-HT1A receptor gene. Deaf-1 was shown to act as transcriptional repressor of the 5-HT1A promoter in pre-synaptic raphe nuclei cell lines, while it activated 5-HT1A promoter expression in post-synaptic cells. Hes-5 on the other hand, remained a transcriptional repressor in all cell types. The activity of both transcription factors was impaired in the presence of the C(-1019)G allele. Moreover, Deaf-1 mediated regulation of the 5-HT1A receptor appeared to be HDAC-dependent. Additionally, I utilized mice lacking a functional Deaf-1 protein, to study the in vivo effects of Deaf-1 on 5-HT1A receptor gene expression. Deaf-1 was shown to bind the mouse 5-HT1A promoter sequence and mediate cell-type specific transcriptional repression or enhancement of 5-HT1A receptor gene expression, similar to that observed using in vitro cell lines. As a result, Deaf-1 knockout mice exhibited upregulation of pre-synaptic 5-HT1A receptor gene, which correlated decreased 5-HT neurotransmission. In conclusion, I have identified a unique mechanism of regulating the 5-HT1A gene expression by Deaf-1, both in vitro and in vivo. I established the importance of the C(1019)G polymorphism in regulating 5-HT1A gene and characterized a novel mouse model for studying the effects of Deaf-1 on the serotonin system.
Keywords: Biology, Molecular.